O mistério de Francisco Peñaranda : a magnífica história de um criptojudeu e seu tesouro oculto na Espanha do século XVI - Bispo, Isis Carolina Garcia (2016)
In Portugal and in Spain, for a very long time a belief was cultivated about the Jews, that when being expelled from the Iberian Peninsula, at the beginning of the Modern Age, hid in certain places treasures to be rescued in posterity. Despite this account being cloaked in an atmosphere of mystery and distorted by imagination, in the hope that many nurture of finding riches in gold and jewels, there is evidence that these hidden riches consisted of censored books since, fleeing to other christian countries, they couldn’t take it with them. So in 1992, to corroborate this account, when in the modest Spanish village of Barracota a house was being remodeled, a “kept treasure”, hid by screens in a space between walls, was found. It was a heterogeneous set of 10 prints, a manuscript and a nômina. From those surprising finding its unveiled by extremeño Professor Fernando Serrano Mangas, that the set of clandestine books was hidden around 1557 by Crypto-jew Doctor Francisco Peñaranda. Therefore, this dissertation seeks to illustrate, starting from the analysis of the works “Alborayque” and “A muito devota oração da emparedada”, the mystic crypto-jewish universe and its paths in the 16th century’s contour. Working in this perspective according to the evidentiary method, proposed by Carlo Ginzburg, to highlight fundamental elements from the world vision of this minority that was the object of persecution by the Modern Inquisition.